EFFECT OF COENZYME Q10 APPLICATION ON POST GINGIVAL CURETTAGE: TRANSFORMING GROWTH FACTOR-β1 LEVEL (TGF-β1) IN GINGIVAL CREVICULAR FLUID - Dahlia Herawati (FKG Unlam, 2023)
Background: Curettage is one of the common periodontitis treatments. Mechanical cleaning of periodontal pocket requires additional materials so the wound healing in the operating area is more optimal. Coenzyme Q10 is one of the ingredients can be used to control levels of Reactive Oxygen Species (ROS). Coenzyme Q10 concentrations of 1:9 and 2:8 in previous studies have been shown to stimulate fibroblast proliferation but its impact on TGF-β1 levels is still unknown. Purpose: to compare the effect of Coenzyme Q10 concentrations 1:9 and 2:8 with PerioQTM on TGF-β1 expression post-curettage. Method: In vivo, study was conducted on 12 periodontitis induced - Oryctolagus cuniculus. Coenzyme Q10 concentrations 1:9 (group I) and 2:8 (group II) were applied post-curettage and the results were compared with PerioQTM (group III). The TGF-β1 was collected from gingival sulcus fluid. It was taken with paper point no. 15 on days 3, -7, and -14 followed by Enzyme-Linked Immunosorbent Assay (ELISA) examination. Data were analyzed with Two-way ANOVA and post hoc test with a significance level of p<0.05. Result: TGF-β1 levels after application of Coenzyme Q10 concentration 1:9 and PerioQTM reached the peak on day 7 and decreased on day 14 while Coenzyme Q10 concentration of 2:8 reached the peak on day 14. Conclusion: The application of these three ingredients affects TGF-β1 levels of gingival sulcus fluid. The expression pattern of TGF-β1 concentration 1:9 is similar to PerioQTM, which reaches a peak at 7 days post-curettage and decreases the day after. Keywords: Coenzyme Q10, Gingival Crevicular Fluid, Periodontitis-Induced, Transforming Growth Factor-β1, Ubiquinone